Knowledge construction in innovative networks for the use of biological inputs in periurban horticultural systems - Catullo, Julio Cesar; Arguello Caro, Evangelina Beatriz; Narmona, Luis; Muñoz, Nacira Belen; Silbert, Violeta; Yosviak, Maria Iohanna; Scifo, Alejo; Prado, Agustín; Pietrarelli, Liliana; Videla, Martín; Serra, Gerardo Victor; Gaona Flores, María Amparo; et al. (INIA (Uruguay) y Facultad de Agronomía, Universidad de la República, 2020)
In order to achieve an agroecological transformation of the proximity conventional food systems such as green belts next to cities, particularly in its technological dimension, an active and synergic interaction between science researchers, rural extensionists and farmers as well as government institutions is needed. Using the “Participatory Action Research” as methodology and the complex system perspective, emerged a multi-actoral process in order to promote sustainable agriculture, environmentally healthier and socially accepted in Cordoba’s peri-urban green belt (Cordoba Province, Argentina). The “Interinstitutional team to support the ecological intensification of food production” emphasized its actions through a “learning by doing” practice, recognizing the relevance of tacit, scientific and situational knowledge, co-constructed between all involved actors throughout the process. In the present work we developed a brief analysis about the current technological and productive reality in the periurban horticultural system at the green belt of Cordoba city, with an interdisciplinary and systemic point of view in order to develop possible solutions to achieve an agroecological transition.